1999
DOI: 10.1046/j.1525-1470.1999.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Minocycline Therapy for Acne Vulgaris: Case Reports and Review of the Literature

Abstract: In order to raise the awareness of the potential side effects that can be induced by minocycline, we report three adolescent girls who experienced serious adverse reactions to this therapy, which was prescribed for acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Clinical symptoms are similar to those of SLE in that arthralgia, arthritis, myalgia, fever, and malaise are often present. 1,23,34,41,[45][46][47] Drug-induced lupus differs from SLE in that there is less of a discrepancy in the male-female ratio, skin involvement is dependent on the specific medication in DIL but is generally less common than in SLE, and renal involvement is comparatively less frequent in DIL than in SLE. 41 Testing positive for ANAs is a common finding in SLE and in DIL.…”
Section: Drug-induced Lupusmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical symptoms are similar to those of SLE in that arthralgia, arthritis, myalgia, fever, and malaise are often present. 1,23,34,41,[45][46][47] Drug-induced lupus differs from SLE in that there is less of a discrepancy in the male-female ratio, skin involvement is dependent on the specific medication in DIL but is generally less common than in SLE, and renal involvement is comparatively less frequent in DIL than in SLE. 41 Testing positive for ANAs is a common finding in SLE and in DIL.…”
Section: Drug-induced Lupusmentioning
confidence: 99%
“…43,48 Because minocycline therapy has the potential for harmful adverse reactions, many authors have confirmed the need for physicians to perform pharmacovigilance, or monitoring of the safety of minocycline drug therapy regimens, to detect serious adverse effects. 4,6,15,16,19,20,25,26,31,34,38,42,[44][45][46]49,50 According to the Guide to Physical Therapist Practice, the initial examination "is a comprehensive screening and specific testing process leading to diagnostic classification, or, as appropriate, to a referral to another practitioner." 2 The inclusion of a comprehensive pharmacovigilance component in the patient examination process augments the ability of the physical therapist to identify when a referral to another practitioner is warranted.…”
Section: Drug-induced Lupusmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral isotretinoin therapy is reserved for the severe, cystic, scarring forms of the disease. The untoward side effect of systemic drugs used for acne, although uncommon, can be serious 8,9 …”
mentioning
confidence: 99%
“…20-22 In order to treat the retina with a systemic treatment regimen of minocycline, the blood plasma levels of the drug would have to be very high over long periods of time. This may needlessly expose the entire body to high doses of the drug and increase the chance of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%